2004
DOI: 10.1007/s00436-004-1169-6
|View full text |Cite
|
Sign up to set email alerts
|

Human and animal fascioliasis in Mazandaran province, northern Iran

Abstract: The fascioliasis situation in humans and livestock of Iranian Mazandaran is analysed for the first time. Coprological studies showed 7.3% and 25.4% global prevalences in sheep and cattle, respectively. Studies in slaughterhouses indicate that sheep and cattle may be the main reservoir species, buffaloes may play local roles in the transmission, and goats and horses probably only participate sporadically. Morphometric studies by computer image analysis showed that forms intermediate between Fasciola hepatica an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 18 publications
5
55
1
Order By: Relevance
“…The prevalence of liver fluke infections recorded in the present study was generally lower than those reported from other regions of Iran including Guilan (Daryani et al 2006), Mazandaran (Moghaddam et al 2004), Khouzestan (Sahba et al 1972), Lorestan (Ezatpour et al 2014), Ardabil (Saffarbani 1999), Fars (Ansari-Lari and Moazzeni 2006), Shahr-e Kord (Manouchehehri Naini and Bagheri 2000) and Tehran Provinces (Khanjari et al 2012).…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…The prevalence of liver fluke infections recorded in the present study was generally lower than those reported from other regions of Iran including Guilan (Daryani et al 2006), Mazandaran (Moghaddam et al 2004), Khouzestan (Sahba et al 1972), Lorestan (Ezatpour et al 2014), Ardabil (Saffarbani 1999), Fars (Ansari-Lari and Moazzeni 2006), Shahr-e Kord (Manouchehehri Naini and Bagheri 2000) and Tehran Provinces (Khanjari et al 2012).…”
Section: Discussioncontrasting
confidence: 61%
“…Thus, the two fasciolid species overlap in many African and Asian countries, although in such cases the ecological requirements of the flukes and their snail intermediate host are distinct (Ashrafi et al 2006). The presence of fasciolosis in Iran has long been known and its prevalence and economic significance has been reported by several researchers (Moghaddam et al 2004;Ansari-Lari and Moazzeni 2006;Ashrafi et al 2006;Borji and Parandeh 2010;Ghazani et al 2008;Oryan et al 2011;Khanjari et al 2014). Although a review of available literature strongly suggests that fasciolosis exists in almost all parts of the country, but its prevalence among domestic animals is higher in the southern part of the country, whereas the number of reported human disease cases is significantly higher in the Northern provinces (Khanjari et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This old disease has a great power of expansion in view of the large colonisation capacities of its fasciolid causal agents as well as the freshwater lymnaeid snail vector species (Mas-Coma et al, 2001). Recent reports indicate that fasciolasis is a reemerging highly pathogenic human infection whose epidemiological picture has changed in recent years (Moghaddam et al, 2004). About 17 million people, most of them are children, are thought to be infected by the liver fluke F. hepatica, including human endemics in Europe, Asia, Africa and America (Hopkins, 1992).…”
Section: Studied Stationsmentioning
confidence: 99%
“…Fasciola gigantica is present mainly in tropical and F. hepatica in temperate areas, while both species overlapped in subtropical areas including Egypt and Iran (Soliman 2008;Mas-Coma et al 2009;Moghaddam et al 2004;Shafiei et al 2014).…”
Section: Introductionmentioning
confidence: 99%